Nonsurgical Method of Treatment of Childhood Phimosis with the use of Topical Betamethasone - Rai, BK (Health Renaissance, 2011)
Background: Topical steroid application is an effective alternative to circumcision for the treatment of infant and childhood phimosis. Materials & method: prospective study in 42 boys under 13 years of age, with non retractable foreskin with asymptomatic and past history of disease in grade 4 to 6 weeks treatment. the success was defined as full and free retraction, or easy retraction limited only by congenital adhesions to the glans. Results: Forty-two patients completed the treatment. Successful retraction was achieved in 14 (33.33%) at 4 weeks and 32(76.19%) after 6 weeks of application. No adverse systemic side effects were noted. Two patients had failed treatment and were enrolled for circumcision. Two patients refused further treatment. Six patients were lost in subsequent to follow-up. Conclusion: Betamethasone 0.10% ointment is an effective alternative, non surgical method of the treatment for the childhood phimosis. Keywords: Chilhood phimosis; betamethasone DOI: 10.3126/hren.v8i3.4211 Health Renaissance, September-December 2010; Vol 8 (No.3);176-180